2006
DOI: 10.1002/app.23936
|View full text |Cite
|
Sign up to set email alerts
|

Surface free energy analysis of poly(HEMA)‐poly(perfluoroacrylate) copolymer networks

Abstract: Copolymer networks of 2-hydroxyethylmethacrylate (HEMA) and 2-(N-ethyl perfluorooctane sulfonamido)ethyl acrylate (FOSEA) were prepared by freeradical polymerization. Ethylene glycol dimethacrylate (EGDM) was used as crosslinker and 2,2Ј-azobisisobutyronitrile (AIBN) was used as radical initiator. HEMA/FOSEA ratio of the copolymer networks changed from 50/1 to 10/1 (mol/mol). The contact angles of water, ethylene glycol, glycerin, diiodomethane, paraffin, and formamide were measured on copolymer surfaces and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Over the glass-transition temperature, because polymers undergo substantial segmental rotations and movements, their surface presents a dynamic nature. In nonpolar environments (e.g., air), the density of hydrophobic groups on the surface increases, whereas in a polar environment, the polar groups are oriented toward the surface, which becomes more energetic. …”
Section: Resultsmentioning
confidence: 99%
“…Over the glass-transition temperature, because polymers undergo substantial segmental rotations and movements, their surface presents a dynamic nature. In nonpolar environments (e.g., air), the density of hydrophobic groups on the surface increases, whereas in a polar environment, the polar groups are oriented toward the surface, which becomes more energetic. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SFE of the laser‐processing surface had a higher polar part than the dispersive part, and the polar part comprised all‐electron donor–acceptor interactions and hydrogen bonding. [ 40 ] This result revealed that the hydrogen bonding and chemical bonding also contributed to the joining. A higher W ad meant that there was a higher affinity and intermolecular force between the laser‐processing surface and the CFRP, and it was easier to form hydrogen and chemical bonding during FLJ.…”
Section: Resultsmentioning
confidence: 96%
“…Surface free energy of experimental liquid. [40] Liquid Total surface tension γ L [mN m À1 ] calculation considerably because the groove with high curvature will have a higher SFE than measured.…”
Section: Adhesion Properties Of Laser-processing Surface and Bonding ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of polymers at surface is substantially altered especially when some solvent molecules induce rearrangements. Totally different to rigid ceramic or metal materials, the composition of the polymer varies also with the depth [139]. The morphology is quite similar for L and OL thin films obtained by MAPLE exhibiting a spatial orientation due to a collective influence of evaporation-induced assembly with the specific linkages of the linear structures of polysaccharides.…”
Section: Nanostructured Levan Thin Filmsmentioning
confidence: 94%